On Data and Its Interpretation - Garfinḳel, Yosef (The Biblical archaeology review, 2021)
I was pleased to see four reputable scholars dedicate such a long discussiona to refuting my putative interpretation of the cultic paraphernalia from Moẓa as those of figurines representing a rider on a horse.b In my iconographic analysis, which was based on similar artifacts from other sites, I further raised the question of whether […]